A Retrospective Perinatal Data Analysis of Immigrant and German Women from Representative Birth Cohorts at the Virchow Hospital, Berlin - Armbrust, R.; von Rennenberg, R.; David, M. (Geburtshilfe und Frauenheilkunde, 2016)
Introduction: The aim of this study was to define and characterise differences in the level of obstetric care provided to immigrant and German women. Materials and Methods: An analysis of the Virchow Hospitalʼs birth registers was conducted for the years 1974, 1984 and 1994. The study population of 5445 patients was grouped according to ancestry/family origin on the basis of a name analysis, and subsequently also according to parity (primiparous or multiparous). On name analysis 2741 women were defined as German, 1598 were grouped as women of Turkish origin and 810 as immigrants of other origin. χ2 tests and Fisherʼs exact test were used for significance testing (significance level p < 0.05), and a logistic regression analysis was performed. Results: Rates of caesarean section, episiotomy, higher grade perineal tears and severe postpartum haemorrhage did not differ between the groups. There were however significant differences in the use of uterine stimulants, analgesics in labour and both local and regional anaesthesia, with women of Turkish origin and other immigrants receiving anaesthesia less, but oxytocin more often. Rooming-in was more common among German primipara and multipara from 1984 onwards. Discussion: This retrospective analysis of three historical birth cohorts showed significant differences in perinatal care between German and immigrant women, presumably reflecting deficits in care. It seems remarkable that this trend has not changed over a time span of three decades despite a continuous increase in immigration and acculturation. A “research paradox”, however, remains: Despite these increasing rates, there are no current or older, prospective or systematic studies of obstetric care in immigrants.
Keywords: immigration; perinatal data; women of Turkish origin